1992
DOI: 10.1073/pnas.89.6.2190
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of chicken C-terminal Src kinase: lack of stable association with c-Src protein.

Abstract: Cloning and sequencing of chicken C-terminal Src kinase (CSK), a tyrosine kinase that phosphorylates the regulatory C-terminal tyrosine residue present on cytoplasmic tyrosine kinases of the Src family, demonstrated a high degree of interspecies conservation as well as src homology 2 and 3 domains N-terminal to the kinase domain. The lack of autophosphorylation sites distinguishes CSK from other tyrosine kinases. CSK is unique and does not belong to a gene family, suggesting that it may phosphorylate other mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 33 publications
2
84
0
Order By: Relevance
“…However, evidence from the literature and our own results eliminated this possibility. First, attempts by others (Sabe et al, 1992) and us (data not shown) have failed to detect strong and stable complexes between Csk and Src. Second, Src isolated after pre-incubation with Csk and ATP-Mg remain inactivated (Stover et al, 1994).…”
Section: Resultsmentioning
confidence: 90%
“…However, evidence from the literature and our own results eliminated this possibility. First, attempts by others (Sabe et al, 1992) and us (data not shown) have failed to detect strong and stable complexes between Csk and Src. Second, Src isolated after pre-incubation with Csk and ATP-Mg remain inactivated (Stover et al, 1994).…”
Section: Resultsmentioning
confidence: 90%
“…It was also shown that all these cells express multiple members of SFK including Yes, Fyn, Lyn and Lck, although there were no dramatic changes in their expressions among them. The activity status of SFK was then assessed with anti-Src pY418 antibody that can recognize autophosphorylated tyrosines of SFKs (SFK pY418), since SFK autophosphorylation is directly associated with its function (Sabe et al, 1992a, b). HCC2998 cells demonstrated only faint signals for SFK autophosphorylation, while HCT15 and HT29 cells showed substantial phosphorylation on SFKs potentially corresponding to c-Src and c-Yes.…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylated C-terminal tyrosine binds intramolecularly to the SH2 domain of SFK, thereby generating an inactive conformation Sabe et al, 1992a). The importance of Csk as a negative regulator for SFK and the absence of functional redundancy have been demonstrated by the observation that Csk knockout mice, which are lethal at prenatal stage, exhibited constitutive activation of multiple SFK members (Imamoto and Soriano, 1993;Nada et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…∆mSos-1, from which the guanine nucleotide exchange domain is deleted, was obtained from Dr. M. Sakaue (Kobe, Japan) [32]. Sos-Pro [33], which contains only the proline-rich carboxyterminal fragment of mSos1, and Csk [34] were from T. van Biesen and R. J. Lefkowitz (Duke University). Dominant negative Grb2 (∆NGrb2), in which the N-terminal SH3 domain is deleted, was from A. M. Pendergast (Duke University) [35].…”
Section: Dna Constructsmentioning
confidence: 99%